2017
DOI: 10.1007/s12975-017-0598-3
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin Attenuates Blood-Brain Barrier Disruption and Hemorrhagic Transformation and Improves Neurological Outcome in Ischemic Stroke Rats with Delayed t-PA Treatment: Involvement of ONOO−-MMP-9 Pathway

Abstract: Tissue plasminogen activator (t-PA) has a restrictive therapeutic window within 4.5 h after ischemic stroke with the risk of hemorrhagic transformation (HT) and neurotoxicity when it is used beyond the time window. In the present study, we tested the hypothesis that baicalin, an active compound of medicinal plant, could attenuate HT in cerebral ischemia stroke with delayed t-PA treatment. Male Sprague-Dawley rats were subjected to middle cerebral artery occlusion (MCAO) for 4.5 h and then continuously received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 71 publications
3
52
0
Order By: Relevance
“…Moreover, the increase in matrix metalloproteinase-9 (MMP-9) during the inflammatory phase of ischemic stroke was related to HT, and a 24 h peak of MMP-9 occurred before PH (34). The inhibition of MMP-9 expression with baicalin could maintain the BBB integrity, attenuate thrombolysis-induced HT and improve the prognosis in patients with acute ischemic stroke (35). Several studies have indicated that neutrophil played an important role in the BBB disruption after stroke (22,36).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the increase in matrix metalloproteinase-9 (MMP-9) during the inflammatory phase of ischemic stroke was related to HT, and a 24 h peak of MMP-9 occurred before PH (34). The inhibition of MMP-9 expression with baicalin could maintain the BBB integrity, attenuate thrombolysis-induced HT and improve the prognosis in patients with acute ischemic stroke (35). Several studies have indicated that neutrophil played an important role in the BBB disruption after stroke (22,36).…”
Section: Discussionmentioning
confidence: 99%
“…Despite that some astrocyte-derived factors maintain the BBB function, some astrocyte-derived factors damage the BBB by inducing endothelial cell apoptosis or decreasing the expression of endothelial tight junctionrelated proteins, which include vascular endothelial growth factor (VEGF) [204][205][206][207], glutamate [208][209][210], endothelins (ETs) [21,211,212], MMP [208,213,214], and nitric oxide (NO) [215,216] (Table 1). As zincendopeptidases, MMPs can directly degrade endothelial tight junction-related proteins and ECM molecules, which promotes angiogenesis whereas simultaneously increases BBB permeability [78,217,218]. And it is through the signaling pathway activating or suppressing MMPs that many other factors such as APOE, NO, and ETs get to affect the BBB integrity [201,212,215].…”
Section: The Bbb Integrity-suppressing Effects Of Astrocytesmentioning
confidence: 99%
“…In a recent study, baicalin administration significantly decreased the mortality rates, and ameliorated BBB disruption and hemorrhagic transformation. In addition, baicalin markedly scavenged peroxynitrite and inhibited MMP-9 expression and activity in MCAO-induced ischemic brains with delayed tissue plasminogen activator treatment [ 86 ]. The effect of baicalin on hyperglycemia-exacerbated cerebral ischemia/reperfusion injury in rats was investigated by Li et al [ 13 ].…”
Section: Neuroprotective Effects Of Baicalinmentioning
confidence: 99%